Penuntasan Hasil Belajar Siswa Kelas XII Melalui Penerapan Strategi Belajar PQ4R pada Konsep Evolusi di SMA Negeri 4 Ambon - Marthinus Usmany (Universitas Islam Negeri Ar-Raniry, 2019)
This study aims to determine student learning outcomes and student responses to PQ4R learning strategies in evolutionary studies. To find out the obstacles that might be found. This research is a class action research design. These results are based on the opinions of Thomas and Robinson; the PQ4R strategy is used to help students understand the contents of the reading and remember the material they have read. The results of this study indicate that the learning process of students in evolutionary material in biology learning with PQ4R learning strategies can complete their learning outcomes and increase the level of student mastery. From the overall learning outcomes for two cycles, the student learning outcomes in evolutionary material by applying the PQ4R learning strategy can improve learning outcomes with completeness percentage of cycle I is 78.57% and cycle II is 85.71%, the element of student interest in cycle I is 45.8% and cycle II 51.8%. The improvement of students 'abilities in evolutionary material through PQ4R learning strategies shows that there is an increase in students' learning motivation through diligence in doing assignments, showing interest in learning, pleasure in working individually and in groups, being able to maintain opinions and looking for and solving questions in evolutionary material.